Shopping for bombs : nuclear proliferation, global insecurity, and the rise and fall of the A.Q. Khan network - Corera, Gordon (Oxford University Press, 2006)
A.Q. Khan was the world's leading black market dealer in nuclear technology, described by a former CIA Director as "at least as dangerous as Osama bin Laden." A hero in Pakistan and revered as the Father of the Bomb, Khan built a global clandestine network that sold the most closely guardednuclear secrets to Iran, North Korea, and Libya. Here for the first time is the riveting inside story of the rise and fall of A.Q. Khan and his role in the devastating spread of nuclear technology over the last thirty years. Drawing on exclusive interviews with key players in Islamabad, London, and Washington, as well as with members of Khan'sown network, BBC journalist Gordon Corera paints a truly unsettling picture of the ultimate arms bazaar. Corera reveals how Khan operated within a world of shadowy deals among rogue states and how his privileged position in Pakistan provided him with the protection to build his unique and deadlybusiness empire. It explains why and how he was able to operate so freely for so many years. Brimming with revelations, the book provides new insight into Iran's nuclear ambitions and how close Tehran may be to the bomb. In addition, the book contains startling new information on how the CIA and MI6 penetrated Khan's network, how the U.S. and UK ultimately broke Khan's ring, and how they persuaded Pakistan's President Musharraf to arrest a national hero. The book also provides the first detailed account of thehigh-wire dealings with Muammar Gadaffi, which led to Libya's renunciation of nuclear weapons and which played a key role in Khan's downfall. The spread of nuclear weapons technology around the globe presents the greatest security challenge of our time. Shopping for Bombs presents a unique window into the challenges of stopping a new nuclear arms race, a race that A.Q. Khan himself did more than any other individual to promote